Unravelling the role of innovation platforms in supporting co-evolution of innovation: Contributions and tensions in a smallholder dairy development programme - Kilelu, C.W.; Klerkx, Laurens; Leeuwis, Cees (Elsevier, 2013)
The agricultural innovation systems approach emphasizes the collective nature of innovation and stresses that innovation is a co-evolutionary process, resulting from alignment of technical, social, institutional and organizational dimensions. These insights are increasingly informing interventions that focus on setting up multi-stakeholder initiatives, such as innovation platforms and networks, as mechanisms for enhancing agricultural innovation, particularly in sub-Saharan Africa. There has been much emphasis on how such platforms are organized, but only limited analysis unravelling how they shape co-evolution of innovation processes. This paper addresses this gap and conceptualizes platforms as intermediaries that connect the different actors in innovation systems in order to foster effective co-evolution. We present a case study of a smallholder dairy development programme in Kenya, led by a consortium of five organizations that provide a platform for building multi-actor partnerships to enhance smallholder dairy productivity and improve livelihoods. The findings indicate that co-evolution of innovation is a highly dynamic process with various interactional tensions and unexpected effects, and that the distributed nature of intermediation is important in resolving some of these tensions emerging at different actor interfaces. However, platforms are not always able to adapt adequately to emerging issues. This points to the need to look at platforms dynamically and pay more attention to mechanisms that strengthen feedback, learning and adaptive management in innovation processes.